Destino do “lixo” no projeto de assentamento bom lugar I: responsabilidades e desafios - Medeiros, Antonia Taizi Costa de (Universidade Federal Rural do Semi-Árido, 2018)
This work is the result of a research that was carried out in Projeto de Assentamento Bom Lugar I (Bom Lugar I Settlement Project) situated in the town of Upanema - RN. The subject of the research is the issue of the destination of "garbage" in Projeto de Assentamento Bom Lugar I: responsibilities and challenges. Thus, the objective of this work was to investigate the perception of the residents of the community regarding the disposal of organic and solid waste, as well as the position of the city hall on this issue. The choice of this matter occurred through my personal experience, when observing the non-existence of garbage collection in the settlement, nor of an appropriate place provided by the public power to put the garbage and waste. The data collection was done through semi-structured, qualitative interviews with the aim of getting closer to the reality of the settlers. The choice of the interviewees was made at random, according to the number of houses in the settlement. For that, six interviews were conducted in general, five of them with people from the community and one with an employee from the city hall of Upanema linked to the collection sector. In this way, it can be analyzed that the destination of the garbage and waste occurs through the incorrect disposal and the solution that the majority of the inhabitants uses to eliminate the unwanted materials are the fires. It is concluded that the main contributions of this work are to make it clear that the settlement and people need subsistence in order to be able to continue living in the countryside.
Monografia
Keywords: Educação ambiental; Zona rural; Descarte de resíduos; Environmental education; Countryside; Disposal of waste; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL